2022
DOI: 10.1093/jn/nxac063
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the Gut Microbiota Composition and Fecal Short-Chain Fatty Acids with Leukocyte Telomere Length in Children Aged 6 to 9 Years in Guangzhou, China: A Cross-sectional Study

Abstract: Background Telomere length serves as a marker of cellular senescence and appears to plateau between the age of 4 years and young adulthood after when gut microbiota is supposed to be established. However, scarce data is known about the correlation between gut microbiota composition and telomere length in pediatric population. Objectives We aimed to investigate whether the gut microbiota and the concentrations of short-chain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Within the Firmicutes phylum, the Family XIII AD3011 group is a classification with unclear characteristics. Previous literature suggested that the gut genus Family XIII AD3011 group exhibited a heightened susceptibility to abdominal aortic aneurysm and was linked to polycystic ovary syndrome, chronic schizophrenia, and telomere shortening (27)(28)(29)(30). There was currently no research on its involvement in ocular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Within the Firmicutes phylum, the Family XIII AD3011 group is a classification with unclear characteristics. Previous literature suggested that the gut genus Family XIII AD3011 group exhibited a heightened susceptibility to abdominal aortic aneurysm and was linked to polycystic ovary syndrome, chronic schizophrenia, and telomere shortening (27)(28)(29)(30). There was currently no research on its involvement in ocular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, research on Family XIII AD3011 group and Clostridiales vadin BB60 is limited. Some studies have shown a positive correlation between Family XIII AD3011 group and leukocyte telomere length, re ecting aging, but it is uncertain whether this effect is related to in ammation 29 . Additionally, the Family XIII AD3011 group is positively correlated with ACOD1 expression levels 29 .…”
Section: Forward Mr Analysismentioning
confidence: 99%
“…Some studies have shown a positive correlation between Family XIII AD3011 group and leukocyte telomere length, re ecting aging, but it is uncertain whether this effect is related to in ammation 29 . Additionally, the Family XIII AD3011 group is positively correlated with ACOD1 expression levels 29 . In contrast, ACOD1 is highly expressed in the colon tissues of UC patients, and its expression is positively correlated with the severity of intestinal in ammation.…”
Section: Forward Mr Analysismentioning
confidence: 99%